Association of gut microbiota with the pathogenesis of SARS-CoV-2 Infection in people living with HIV - Ishizaka, Aya; Koga, Michiko; Mizutani, Taketoshi; Yamayoshi, Seiya; Iwatsuki-Horimoto, Kiyoko; Adachi, Eisuke; Suzuki, Yutaka; Kawaoka, Yoshihiro; Yotsuyanagi, Hiroshi (BMC microbiology, 2024)
People living with HIV (PLWH) with chronic inflammation may have an increasing risk for coronavirus disease 2019 (COVID-19) severity; however, the impact of their gut microbiota on COVID-19 is not fully elucidated. Here, we analyzed the temporal changes in the gut microbiota composition of hospitalized severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected PLWH (PLWH-CoV) and their correlation with COVID-19 severity. The 16S rRNA analysis results using stool samples (along the timeline from disease onset) from 12 hospitalized PLWH-CoV, whose median CD4 + T cell count was 671 cells/µl, were compared to those of 19 healthy people and 25 PLWH. Bacterial diversity in PLWH-CoV is not significantly different from that of healthy people and SARS-CoV-2 non-infected PLWH, but a significant difference in the microbiota diversity was observed in the classification according to the disease severity. Immediately after the disease onset, remarkable changes were observed in the gut microbiota of PLWH-CoV, and the changing with a decrease in some short-chain fatty acid-producing bacteria and an increase in colitis-related pathobiont. In the second week after disease onset, relative amounts of specific bacteria distinguished between disease severity. One month after the disease onset, dysbiosis of the gut microbiota persisted, and the number of Enterobacteriaceae, mainly Escherichia-Shigella, which is potentially pathogenic, increased and were enriched in patients who developed post-acute sequelae of COVID-19 (PASC). The changes in the gut microbiota associated with SARS-CoV-2 infection observed in PLWH in this study indicated a persistent decrease in SCFA-producing bacteria and an intestinal environment with an increase in opportunistic pathogens associated with enteritis. This report demonstrates that the intestinal environment in PLWH tends to show delayed improvement even after COVID-19 recovery, and highlights the importance of the dysbiosis associated with SARS-CoV-2 infection as a potential factor in the COVID-19 severity and the PASC in PLWH.